2008
DOI: 10.1093/eurheartj/ehn248
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between lipid volume in the target lesion, measured by integrated backscatter intravascular ultrasound, and post-procedural myocardial infarction in patients with elective stent implantation

Abstract: A larger plaque volume and lipid-rich plaque may be indicative of embolic events after stent implantation, resulting in myocardial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 24 publications
4
54
1
3
Order By: Relevance
“…The proportion of post-procedural myocardial injury was higher than in the previous report, accounting for 11% 9) . The cut-off value of TnT in the previous study was 0.3 ng/mL, and different definitions of post-procedural myocardial injury may explain these discrepancies.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…The proportion of post-procedural myocardial injury was higher than in the previous report, accounting for 11% 9) . The cut-off value of TnT in the previous study was 0.3 ng/mL, and different definitions of post-procedural myocardial injury may explain these discrepancies.…”
Section: Discussioncontrasting
confidence: 76%
“…A recent study showed that a larger volume and lipid-rich plaque on IB-IVUS might be indicative of post-procedural myocardial injury in elective PCI 9) . Intense yellow plaques upon angioscopic examination correlated with the presence of a plaque with a large lipid area on IB-IVUS display 14) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These complications may include plaque shift and distal embolization of plaque debris, which could impair clinical outcomes [6]. There is emerging evidence that the reduction of the lipid content of LRPs is associated with the occurrence of distal embolization [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%